Historical and Current Trends in Colon Trauma - Causey, Marlin Wayne; Rivadeneira, David E.; Steele, Scott R. (Clinics in Colon and Rectal Surgery, 2012)
The authors discuss the evolution of the evaluation and management of colonic trauma, as well as the debate regarding primary repair versus fecal diversion. Their evidence-based review covers diagnosis, management, surgical approaches, and perioperative care of patients with colon-related trauma. The management of traumatic colon injuries has evolved significantly over the past 50 years; here the authors describe a practical approach to the treatment and management of traumatic injuries to the colon based on the most current research. However, management of traumatic colon injuries remains a challenge and continues to be associated with significant morbidity. Familiarity with the different methods to the approach and management of colonic injuries will allow surgeons to minimize unnecessary complications and mortality.
Keywords: colon trauma; colon injury; damage control laparotomy; perioperative colon trauma care